Integrated Network Pharmacology Analysis and Experimental Validation to Investigate the Mechanism of Zhi-Zi-Hou-Po Decoction in Depression - Bai, Yongtao; Zhang, Yingchun; Li, Shuolei; Zhang, Wenzhou; Wang, Xinhui; He, Baoxia; Ju, Wenzheng (Frontiers in Pharmacology, 2021)
Zhi-Zi-Hou-Po Decoction (ZZHPD) is a well-known traditional Chinese medicine (TCM) that has been widely used in depression. However, the antidepressant mechanism of ZZHPD has not yet been fully elucidated. The purpose of this study was to explore the pharmacological mechanisms of ZZHPD acting on depression by combing ultra-flow liquid chromatography coupled with quadrupole time-of-flight mass spectrometry (UFLC-Q-TOF/MS) and network pharmacology strategy. The chemical components of ZZHPD were identified using UFLC-Q-TOF/MS, while the potential drug targets and depression-related targets were collected from databases on the basis of the identified compounds of ZZHPD. Protein-protein interaction (PPI) network, GO and KEGG pathway enrichment analysis were used to unravel potential antidepressant mechanisms. The predicted antidepressant targets from pharmacology-based analysis were further verified in vivo. As a result, a total of 31 chemical compounds were identified by UFLC-Q-TOF/MS; 514 promising drug targets were mined by using the Swiss Target Prediction and 527 depression-related target genes were pinpointed by the GeneCards and OMIM databases. STRING database and Cytoscape’s topological analysis revealed 80 potential targets related to the antidepressant mechanism of ZZHPD. The KEGG pathway analysis revealed that the antidepressant targets of ZZHPD were mainly involved in dopaminergic synapse, serotonin synapse, cAMP, and mTOR signaling pathways. Furthermore, based on the animal model of depression induced by chronic corticosterone, the regulatory effects of ZZHPD on the expression of MAOA, MAOB, DRD2, CREBBP, AKT1, MAPK1, HTR1A and GRIN2B mRNA levels as well as the cAMP signaling pathway and monoaminergic metabolism were experimentally verified in rats. Our study revealed that ZZHPD is expounded to target various genes and pathways to perform its antidepressant effect.